2017
DOI: 10.1016/j.nmd.2017.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Timing and localization of human dystrophin isoform expression provide insights into the cognitive phenotype of Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a muscular dystrophy with high incidence of learning and behavioural problems and is associated with neurodevelopmental disorders. To gain more insights into the role of dystrophin in this cognitive phenotype, we performed a comprehensive analysis of the expression patterns of dystrophin isoforms across human brain development, using unique transcriptomic data from Allen Human Brain and BrainSpan atlases. Dystrophin isoforms show large changes in expression through life wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 47 publications
2
61
0
Order By: Relevance
“…The restrictive ventilatory defect in DMD is caused by the absence of full‐length dystrophin in the diaphragm and other respiratory muscles. While defects of short dystrophin isoforms have been associated with increased risk of intellectual disability and other central nervous system (CNS) manifestations of DMD, 28–30 they have not been clearly linked to more severe muscle weakness. A possible explanation is that while patients with very severe cognitive deficiencies are excluded from PFTs, because of insufficient cooperation, patients with subtler CNS issues due to Dp140/Dp71 defects still perform worse in PFTs, which are largely influenced by volition and effort.…”
Section: Discussionmentioning
confidence: 99%
“…The restrictive ventilatory defect in DMD is caused by the absence of full‐length dystrophin in the diaphragm and other respiratory muscles. While defects of short dystrophin isoforms have been associated with increased risk of intellectual disability and other central nervous system (CNS) manifestations of DMD, 28–30 they have not been clearly linked to more severe muscle weakness. A possible explanation is that while patients with very severe cognitive deficiencies are excluded from PFTs, because of insufficient cooperation, patients with subtler CNS issues due to Dp140/Dp71 defects still perform worse in PFTs, which are largely influenced by volition and effort.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the expression of Dp260 in mdx /utrnK/K mice can rescue the mdx phenotype (146), indicating overlapping functions between Dp427m and Dp260. On the other hand, it is now well established that a third of DMD patients display cognitive deficiencies – which might be correlated with mutations affecting Dp140 (147) – attesting that dystrophin can be involved in other cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Duchenne's muscular dystrophy), is important to consider as well as it is the top scoring upstream regulator pathway in Purkinje cells, and is also significant in granule cells. Dystrophin is an extremely large protein expressed from multiple promoters 208,209 and its loss in muscle causes Duchenne muscular dystrophy.…”
Section: A Seventh Common Upstream Regulatory Pathway Dmd (Dystrophimentioning
confidence: 99%